ON THE ORIGIN OF HIGH-ALUMINA ARC BASALT AND THE MECHANICS OF MELT EXTRACTION - Brophy James G.; Marsh Bruce D. (My University, 1986)
Most models of high-alumina arc basalt petrogenesis rely heavily on the supposition that the abundances of certain trace elements, in particular the relatively unfractionated Rare Earth Element (REE) patterns and the unusually high concentrations of K, Rb, Sr, and Ba are incompatible with a garnet-bearing subducted oceanic crustal (quartz eclogite) source rock. We have carefully examined this apparently unequivocal evidence in light of recent progress on the physics of melt extraction and the heat transfer and mechanics of magma ascent. The weakest element of all trace element models involving a quartz eclogite source is the assumption that the element concentrations are fixed at the source and only later modified in the near-surface environment. We expand on such models by monitoring the concentrations of REE and major and trace elements during initial melting, ascent, and extraction of magma. This is done by combining calculated cooling curves for ascending magmatic bodies with high pressure phase equilibria. The amount that each phase contributes to the melt is monitored along with the composition of the melt and residual solids. With quartz eclogite, initial melting initiates gravitational instability of the entire source material (melt plus solids) before melt extraction can occur. During ascent of this mush, melting increases until the solids can be repacked to free the melt. This extraction takes place some 15–20 km above the slab, after about 50 per cent melting, at which point the melt has a pattern of REE and other trace element concentrations almost identical to those observed in high-alumina arc basalts, assuming an initial composition equivalent to altered oceanic crust plus 5 per cent pelagic sediment. Sr abundances are the only ones which are not well-matched by this process. The major element concentrations of the extracted melt also closely match those of high-alumina arc basalt. A similar, but less detailed evaluation of both fertile and depleted peridotite source rocks yields good agreement for the REE and other trace element concentrations assuming a LREE-enriched source rock strongly enriched in K, Rb, Sr, and Ba. Ni, Cr, and Co abundances are satisfied only through substantial low pressure fractionation of mafic phases, in particular olivine. Though not rigorously tested, such a process may be compatible with the observed major element concentrations of high-alumina basalt. However, the experimentally verified fact that high-alumina basalts could never have been in equilibrium with either an olivine-bearing magma or source rock eliminates this possibility altogether. Thus, the simultaneous consideration of the mechanics of ascent and melt extraction along with phase equilibria clearly shows that partial melting of quartz eclogite best satisfies the chemical constraints of major, trace, and REE characteristics of high-alumina arc basalts.